INCLUSIVITY OF REGIONAL GOVERNMENT PUBLIC POLICY IN THE REVISION OF THE REGIONAL REGIONAL RTRW OF SUMENEP DISTRICT - Al Fuadi, Moh Mahshun (DIA: Jurnal Administrasi Publik, 2025)
The inclusiveness of regional government policies can create policies that are not only legal and effective, but also support sustainable development that supports justice and equality, especially in the formulation of revised Regional Spatial Planning (RTRW). Therefore, public involvement in formulating this RTRW Regional Regulation is a very important focus, public in the sense of not only civil society (Community) but also all elements from Academics, Entrepreneurs, Non-Government Organizations (NGOs), Environmental Activists so that the resulting formulation is in accordance with expectations of the interests of society. Public policy inclusiveness refers to an approach in designing and implementing policies that ensures equal participation, benefits and protection for all levels of society, regardless of differences or discrimination and can increase social justice, reduce disparities and build a stronger and more sustainable society. The method used in this research is qualitative with a descriptive type. The activity carried out by the author in this activity is to collect data that is closely related to the processes and stages of regional government policy inclusiveness in the RTRW Regional Regulation, which can be used as a grand theory or theory for basic reference in answering the problem formulation. How is public involvement in the formulation of revisions to the RTRW Regional Regulation.